Comparison of in vivo activity of fluconazole with that of amphotericin B against Candida tropicalis, Candida glabrata, and Candida krusei. - Fisher, M A (1989)
Fluconazole (UK-49,858) is a new oral bis-triazole antifungal agent with demonstrated activity against Candida albicans. Because of the increasing importance of infections due to other species of Candida, we studied the efficacy of fluconazole in a rat model of established systemic candidiasis, using clinical isolates of C. tropicalis, C. glabrata, and C. Krusei. In normal rats, oral fluconazole at both 20 and 80 mg/kg per day for 7 days reduced both kidney and liver titers of C. tropicalis and C. glabrata compared with those in control animals and was only slightly inferior to amphotericin B. Both fluconazole and amphotericin B were ineffective in reducing kidney titers of C. krusei, but amphotericin B was more effective than fluconazole in reducing liver titers. Fluconazole showed no increased efficacy at the higher dose of 80 mg/kg per day compared with 20 mg/kg per day in any experiment. These results suggest that oral fluconazole may be useful in the treatment of established disseminated candidiasis caused by species other than C. albicans. Further in vivo studies are needed, however, to define minimum effective doses and length of therapy and to test additional Candida isolates.